Retroperitoneal Abcess Profiles in a Tertiary Hospital in Bandung, Indonesia : Long Term Retrospective Study - Daniel Saputra; Ricky Ardiansjah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Retroperitoneal abscess is a rare and difficult-to-diagnose condition. The delay in diagnosis is the primary cause of mortality. We did a case series investigation to describe the profiles of retroperitoneal abscesses. We obtained retrospective data from medical records. We reviewed thirty patients admitted to our hospital with retroperitoneal abscesses from January 2013 to December 2019. Of 30 patients reviewed, 56.67% were male, with 50.14 years-old mean age. Approximately 46.67% presented with a chief complaint of back pain, and about 63.33% of cases had a fever. The most prevalent source was genitourinary, which accounted for 60% of the cases. The most common type of abscess was the perirenal abscess. Diabetes mellitus, malignancy, and an immunocompromised condition were all prevalent comorbidities. Escherichia coli was the most prevalent pathogen (46.66%), followed by Klebsiella pneumoniae (26.67%). For genitourinary abscesses, percutaneous drainage was typically used, whereas surgical drainage was recommended for gastrointestinal abscesses. The mortality rate of those conditions was 13.33%. Retroperitoneal abscesses have a wide range of clinical manifestations and causes. The treatment for retroperitoneal abscesses differed depending on the etiology and severity of the infection.